2015
DOI: 10.1093/hmg/ddv484
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of polycystin-L causes hippocampal and thalamocortical hyperexcitability

Abstract: Epilepsy or seizure disorder is among the least understood chronic medical conditions affecting over 65 million people worldwide. Here, we show that disruption of the polycystic kidney disease 2-like 1 (Pkd2l1 or Pkdl), encoding polycystin-L (PCL), a non-selective cation channel, increases neuronal excitability and the susceptibility to pentylenetetrazol-induced seizure in mice. PCL interacts with β2-adrenergic receptor (β2AR) and co-localizes with β2AR on the primary cilia of neurons in the brain. Pkdl defici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 53 publications
0
34
0
Order By: Relevance
“…Polycystin-L (PCL), a Ca 2+ -permeable channel encoded by PKD2-like 1 and related to Polycystin 2, is expressed in the primary cilia of neuronal cells of the brain and its loss of function leads to decreased cyclic AMP production and neuronal excitability (Gross and Ferrendelli, 1979). Yao et al (2016) showed that loss of PCL causes increased neuronal hyperexcitability and susceptibility to seizures in mice, thus implicating primary cilia in EDs. Our findings point to a conserved function of PKD genes in cilia-mediated signaling of neurons and in seizure-like disorders.…”
Section: Soxb1-2 Expression Marks Adult Ectodermal-lineage Progenitorsmentioning
confidence: 99%
“…Polycystin-L (PCL), a Ca 2+ -permeable channel encoded by PKD2-like 1 and related to Polycystin 2, is expressed in the primary cilia of neuronal cells of the brain and its loss of function leads to decreased cyclic AMP production and neuronal excitability (Gross and Ferrendelli, 1979). Yao et al (2016) showed that loss of PCL causes increased neuronal hyperexcitability and susceptibility to seizures in mice, thus implicating primary cilia in EDs. Our findings point to a conserved function of PKD genes in cilia-mediated signaling of neurons and in seizure-like disorders.…”
Section: Soxb1-2 Expression Marks Adult Ectodermal-lineage Progenitorsmentioning
confidence: 99%
“…TRPP3 is expressed in the brain (14), and a recent study using TRPP3 knock-out mice found that disruption of TRPP3 causes hippocampal and thalamocortical hyperexcitability and increases susceptibility to pentylenetetrazol-induced seizures (47). Interestingly, several neural proteins, including various G-protein-coupled receptors and ion channels that control the excitability of neurons, have now been reported to be dynamically regulated by palmitoylation (48).…”
Section: Discussionmentioning
confidence: 99%
“…It would be interesting to see whether palmitoylation of TRPP3 at Cys-38 represents a mechanism underlying the control of TRPP3 channel activity in neurons with respect to neuronal excitability. TRPP3 was also found to interact with ␤2-adrenoreceptor (␤2AR) and co-localize with ␤2AR in the brain (47). Binding of agonist isoproterenol to ␤2AR was reported to markedly reduce the palmitoylation of the associated G␣ s (49).…”
Section: Discussionmentioning
confidence: 99%
“…TRPP3, also called polycystin-L (PKDL) or polycystin-2L1 (PKD2L1), is localized to primary cilia (53, 66) and the centrosome (67). TRPP3 is a calcium channel with a high homology with TRPP2 (68).…”
Section: Ciliary Calcium Channelsmentioning
confidence: 99%
“…A very recent study by Zhou's group indicates that TRPP3 in the neuronal primary cilium regulates neuronal excitability and susceptibility to pentylenetetrazol-induced seizure in mice (66). The group showed that TRPP3 interacts with the β2 adrenergic receptor and that the receptor-channel complex regulates cAMP response element-binding protein.…”
Section: Ciliary Calcium Channelsmentioning
confidence: 99%